Pengembangan perangkat lunak optimasi ekonomi dan analisa finansial PLTS studi kasus PLTS 10 MWAC - Apri Setiawan; Agus Hermanto (Jurnal Teknik Mesin Indonesia, 2022)
Financial analysis is an analysis that compares costs and benefits to determine whether a project can generate profits over the life of the project. In conducting financial analysis there are several investment feasibility criteria that are commonly used, namely, Net Present Value (NPV), Internal Rate Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). This study aims to develop a financial analysis software for Solar Power Plants which includes cost analysis of investment components (A, B, C, D, & E) and is made using Visual Basic for Application (VBA). In this research, a case study of financial analysis of PLTS 10 MWAC using software that the author developed, then obtained the NPV value of Rp. 939,928,554 > 0, BCR 1.01 > 1, IRR 8.87 % > Weight Average Cost of Capital (WACC) 8.76 %, and Payback Period 9 Years 8 Months < 25 Years (Project life), So it can be concluded that PLTS 10 MWAC is feasible to work on.